Optimizing the Role of Digital Marketing through Digital Road trip to Acceleration Tajuk Tourism Village Pilot Projects: Optimalisasi Peran Digital Marketing melalui Digital Roadtrip Dalam Rangka Mendorong Akselerasi Rintisan Desa Wisata Tajuk - Hawik Ervina Indiworo; Efriyani Sumastuti; Dhea Rizky Amelia (Yayasan Ahmar Cendekia Indonesia, 2022)
Digital Marketing is needed to encourage the acceleration of the Tajuk Tourism Village Pioneer. By using a digital roadtrip model through Instagram, it turns out to be able to promote tourism potential in Tajuk Village, because its main feature is that it features images and videos, so that Instagram users feel they are in the Tajuk Village Tourism Area. Training activities on the use of digital marketing are carried out for young people, as the largest proportion of active Instagram users. With the training carried out, the Tajuk Village youth group can independently design Instagram content for promotional purposes. In the context of accelerating the Pioneer of the Tajuk Tourism Village, a comprehensive synergy is needed from all levels of society. The trick is to encourage active Instagram users in Tajuk Village to follow